Pertinencia de los programas de pregrado de la Universidad Católica de Pereira y comportamiento de los graduados en el mercado laboral del área metropolitana, durante el período 2010-2015 (2019)
Between the different requirements from the top throughout its history education,issues of relevance and quality, as criteria that underlie the ability of understandingthe nature of the environment and trends, and the answer highlights the differentsocial needs. In this context, higher education becomes a prime interpreter in theanalysis and explanation of the complexity of social change in the context of aglobalized and interdependent world, highly vulnerable and uncertain. In addition, and particularly, higher education must engage in relevance withthe integral formation of the human person, understood as being perfectible,complex and multidimensional that exalts the axiological foundation (ethical andmoral positions) in making decisions that result the common good, democraticattitudes and human development. Therefore, this article focuses on inquiring about the relevance of differentundergraduate programs at the Catholic University of Pereira, and laborimmersion graduates in 2010-2015.